Al-Manhâj al-Fiqhî ‘Inda Jamâ’ah “Muassah al-Da’wah al-Islâmiyah al-Indûnîsiyah” (Lembaga Dakwah Islam Indonesia) wa Âtsâruhu Fî Istinbâth al-Ahkâm al-Syar’iyyah - Moh. Abdul Kholiq Hasan; Iskandar Dzulkarnain; Muh. Nashirudin (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2021)
Indonesian Islamic Da’wa Institution or Lembaga Dakwah Islam Indonesia (LDII) tends to embrace exclusivity and takfiri ideology. Though the group denied the claim, evidences from their fiqh manhaj foundation said the opposite. Employing library research method in descriptive qualitative fashion, this article attempts to address this issue by revealing the fiqh manhaj LDII employs and its influences over the legal decisions LDII takes. Content analysis in tandem with document triangulation and structured interviews was applied to investigate the textual references LDII uses. The findings indicate that LDII employs a fiqh manhaj called manqul, knowledge transmission centered around LDII founder – Nur Hasan ‘Ubaidah. This manhaj is influential for LDII in issuing legal decisions which tend to be exclusive and takfiri. In some cases, the fiqh manhaj of LDII was considered to be contradictory against ahlus sunnah fiqh manhaj which embraces openness and non-takfiri ideology.